Gastric Bypass Promotes More Lipid Mobilization Than a Similar Weight Loss Induced by Low-Calorie Diet - Joel Kullberg; Magnus Sundbom; Arvo Haenni; Susanne Freden; Lars Johansson; Peter Börnert; Anders Ahlström; Håkan Ahlström; Anders Karlsson (Journal of Obesity)
Background. Recently, we found large reductions in visceral and subcutaneous fat one month after gastric bypass (GBP), without any change in liver fat content. Purpose. Firstly to characterize weight loss-induced lipid mobilization after one month with preoperative low-calorie diet (LCD) and a subsequent month following GBP, and secondly, to discuss the observations with reference to our previous published findings after GBP intervention alone. Methods. 15 morbidly obese women were studied prior to LCD, at GBP, and one month after GBP. Effects on metabolism were measured by magnetic resonance techniques and blood tests. Results. Body weight was similarly reduced after both months (mean: −8.0 kg, n=13). Relative body fat changes were smaller after LCD than after GBP (−7.1±3.6% versus −10±3.2%, P=.029, n=13). Liver fat fell during the LCD month (−41%, P=.001, n=13) but was unaltered one month after GBP (+12%). Conclusion. Gastric bypass seems to cause a greater lipid mobilization than a comparable LCD-induced weight loss. One may speculate that GBP-altered gastrointestinal signalling sensitizes adipose tissue to lipolysis, promoting the changes observed.